2017
DOI: 10.1097/md.0000000000008675
|View full text |Cite
|
Sign up to set email alerts
|

The correlational research among serum CXCL13 levels, circulating plasmablasts and memory B cells in patients with systemic lupus erythematosus

Abstract: We investigated whether serum CXC ligand 13 protein (CXCL13) levels correlate with the circulating plasmablasts and memory B-cells alteration in systemic lupus erythematosus (SLE) patients. The diagnostic use of CXCL13 concentrations in active lupus was also analyzed.A total of 36 SLE patients and 18 healthy controls were included. Serum CXCL13 levels were examined by enzyme-linked immunosorbent assay. The frequency and absolute count of circulating plasmablasts and memory B cells were analyzed by flow cytomet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 19 publications
1
5
0
1
Order By: Relevance
“…CXCL13 is found in human blood, plasma and serum and high CXCL13 levels have been associated with pSS and systemic lupus erythematosus (SLE) [18][19][20][21]. A previous study that included patients from the Assessment of Systemic Signs and Evolution of Sjögren's Syndrome (ASSESS) cohort showed that serum CXCL13 and CCL11 levels were elevated in pSS patients with high EULAR Sjögren's Syndrome Disease Activity Index (ESSDAI) score, B-cell activation and NHL [19].…”
Section: Introductionmentioning
confidence: 99%
“…CXCL13 is found in human blood, plasma and serum and high CXCL13 levels have been associated with pSS and systemic lupus erythematosus (SLE) [18][19][20][21]. A previous study that included patients from the Assessment of Systemic Signs and Evolution of Sjögren's Syndrome (ASSESS) cohort showed that serum CXCL13 and CCL11 levels were elevated in pSS patients with high EULAR Sjögren's Syndrome Disease Activity Index (ESSDAI) score, B-cell activation and NHL [19].…”
Section: Introductionmentioning
confidence: 99%
“…Serum CXCL13 levels are found to be significantly higher in SLE patients, especially in those with renal involvement, as compared with healthy controls (83,84). Serum CXCL13 is positively correlated with the SLE Disease Activity Index (SLEDAI) (84,144,145), anti-double-stranded DNA (anti-dsDNA) antibodies titers, and prevalence of inflammatory arthritis, while it is inversely correlated with serum levels of complement factors C3 and C4 (146)(147)(148). CXCL13 is also a potential differentiation marker to identify active SLE from inactive SLE, and to identify LN from non-LN in SLE patients (148).…”
Section: Cxcl13/cxcr5 Axis In Systemic Lupus Erythematosusmentioning
confidence: 99%
“…To gain insight about functional roles of these cells and considering that the expression of chemoreceptors plays an important role in the activation and maturation of B cells, we evaluated the expression of CXCR3, CCR7 and CXCR5 associated with extra-follicular/follicular pathway, to characterize the putative activation/effector sites of the CD21 hi population. An increase in B cells’ CXCR5 expression has been demonstrated when high levels of serum CXCL13 are detected in patients with SLE and nephropathy ( 31 33 ). Conflictingly, it has been stated that higher frequencies of CXCR5 - CXCR3 + B cells correlate with active SLE, besides the presence of CXCR3 + B cells in human kidney tissue ( 18 , 34 , 35 ).…”
Section: Discussionmentioning
confidence: 99%
“…As ABCs and the recently defined DN subset DN2 (ABCs-like phenotype) have been characterized by a high expression of CXCR3 in contrast to CXCR5 ( 10 , 14 , 21 ), our results regarding these cells correspond to those defining a CXCR3 + CXCR5 -/lo CCR7 - phenotype for ABCs. On the other hand, the neglected CD21 hi subset that possesses a higher density of CXCR5 and increases in frequency in post-treatment LN patients, would represent those cells mentioned in the CXCL13/CXCR5 axis reports ( 31 33 ). Perhaps by responding to CXCL13, these lymphocytes could migrate towards tertiary lymphoid aggregates to exert putative tissue-associated functions; or maybe, this phenotype could be associated with a follicular pathway that these cells need to follow to be adequately immunologically trained as memory precursors.…”
Section: Discussionmentioning
confidence: 99%